A late self-portrait of Michelangelo Buonarroti (1475-1564) in the cartoon of the Epifania in the British Museum - de Campos, Deivis; Buso, Luciano (Acta Biomedica Atenei Parmensis, 2020)
The scientific literature has shown that the renowned Italian Renaissance artist and genius of human anatomy Michelangelo Buonarroti (1475-1564) included his self-portrait into some of his most famous works. It has been suggested that the various self-portraits and self-caricatures the artist used in his works over the years may offer some insight into Michelangelo’s physical form and, consequently, provide evidence of his health at different stages of his life. Accordingly, this manuscript presents new evidence [based on facial features described by Daniele of Volterra (1509-1566) and Giorgio Vasari (1511-1574)] that Michelangelo may have inserted his self-portrait into one of the figures that make up the Epifania cartoon, made by the artist in 1553, which is currently in the collection of the British Museum in London, England. Thus, the information contained in this manuscript is not only useful for future analyses of Michelangelo’s health [based on facial features] when he was approximately 78 years old, but also how the artist, who was known for being very introspective, saw himself physically in his old age.